2010
DOI: 10.1111/j.1469-8749.2009.03478.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of motor control in handwriting difficulties in children with or without developmental coordination disorder

Abstract: Aim  The purpose of this study was to characterize handwriting deficits in children with developmental coordination disorder (DCD) using computerized movement analyses. Method  Seventy‐two children (40 females, 32 males; mean age 7y, SD 7mo; range 6y 2mo to 7y 11mo) with handwriting deficits (33 with DCD, 39 without DCD); and 22 age‐ and sex‐matched children without handwriting deficits were asked to perform handwriting tasks on a digital tablet for the collection of kinematic and kinetic data. Practice times … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 22 publications
5
69
0
1
Order By: Relevance
“…Additionally, it was found that the children with dyslexia and co-morbid attention deficits and/or fine motor clumsiness experienced more difficulties in handwriting speed. This finding aligned well with the previous studies on Chinese children with ADHD (e.g., Shen, Lee, & Chen, 2012) and DCD (e.g., Chang & Yu, 2010) regarding their prolonged time in performing copying tasks. By using adjusted multivariate analyses, it was found that their overall difficulties in performing Chinese word dictation tasks were mainly contributed by their poor lexical knowledge of Chinese characters, while their difficulties in performing copying tasks were mainly associated with RAN deficits and individual differences in saccadic efficiency and VMI ability.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, it was found that the children with dyslexia and co-morbid attention deficits and/or fine motor clumsiness experienced more difficulties in handwriting speed. This finding aligned well with the previous studies on Chinese children with ADHD (e.g., Shen, Lee, & Chen, 2012) and DCD (e.g., Chang & Yu, 2010) regarding their prolonged time in performing copying tasks. By using adjusted multivariate analyses, it was found that their overall difficulties in performing Chinese word dictation tasks were mainly contributed by their poor lexical knowledge of Chinese characters, while their difficulties in performing copying tasks were mainly associated with RAN deficits and individual differences in saccadic efficiency and VMI ability.…”
Section: Discussionsupporting
confidence: 92%
“…Studies show children with DCD perform poorly at school as they struggle to master the basic motor skills such as writing legibly, using scissors and completing other manual tasks [31]. In addition, performance in physical education classes or gym may also be difficult and maintaining good sitting posture at a desk in class may be challenge [51].…”
Section: Major Life Areas-educationmentioning
confidence: 99%
“…Handwriting difficulties are mentioned in the formal diagnostic criteria for DCD (APA, 2000), are frequently mentioned in parent and teacher reports and are the most common reason for referral to occupational therapy for this population (Asher, 2006). Despite this, surprisingly little research has been conducted to investigate handwriting difficulties in children with DCD, most of which, has been conducted in alphabets outside the Latin base (Rosenblum & Livneh-Zirinski, 2008;Chang & Yu, 2010), with very different demands such as writing from right to left and producing different types of letter-shapes (Hebrew & Taiwanese). This poses considerable barriers when attempting to inform best practice in countries using the Latin alphabet.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported in the literature that children with DCD demonstrate a distinct slowness (produce less text and take longer to produce letter strokes) across a range of handwriting tasks, including copying (Rosenblum et al, 2003;Rosenblum & Livneh-Zirinski, 2008;Chang & Yu, 2010), writing from memory (Rosenblum et al, 2003, Chang & Yu, 2010 and the habitual task of writing ones name (Rosenblum & Livneh-Zirinski, 2008). However, it is not known to what extent these findings can be applied to the Latin based alphabets.…”
Section: Introductionmentioning
confidence: 99%